2016
DOI: 10.11144/javeriana.cdr13-77.sprw
|View full text |Cite
|
Sign up to set email alerts
|

Service provision in rural water supplies: analysis of four community-based systems in Colombia

Abstract: Community management is the tendency to provide water to rural areas worldwide. Despite the diversity of rural communities and their water supplies, policies tend to be uniform, failing to be effective. Four rural water supplies in the Colombian Andes were studied combining quantitative and qualitative methods. Aspects of infrastructure, training of human resources, revenue collection, water quality and post-construction support were studied. The study provides evidence on the need to design policies and progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…A significant number of publications have confirmed the need for constant post-construction support from external agencies regarding technical, managerial and financial aspects to ensure the long-term sustainability and functionality of RWSS [20][21][22][23][24][25][26]. In a study developed in Dominican Republic, Schweitzer and Mihelcic [27] found that the frequency of technical visits from external agencies responsible to offer support to rural service providers was positively related to communities where a strong financial scheme persisted.…”
Section: Critical Factors For Community Management Success In the Literaturementioning
confidence: 99%
“…A significant number of publications have confirmed the need for constant post-construction support from external agencies regarding technical, managerial and financial aspects to ensure the long-term sustainability and functionality of RWSS [20][21][22][23][24][25][26]. In a study developed in Dominican Republic, Schweitzer and Mihelcic [27] found that the frequency of technical visits from external agencies responsible to offer support to rural service providers was positively related to communities where a strong financial scheme persisted.…”
Section: Critical Factors For Community Management Success In the Literaturementioning
confidence: 99%
“…When addressing sustainability in RWSS, the literature has emphasized the importance of understanding challenges for different contexts [46]. The results from this study show that challenges to sustainable water provision in the assessed system are like those described elsewhere [5,9,40,53,55,60] and in Colombia [61,62] in relation to the lack of training, knowledge, and compliance with legal standards and regulations, weak finances to properly develop system administration, operation, and maintenance, and a lack of post-construction support. As in other places, productive uses of water, typical in rural areas, were ignored in the system design, which created technical and managerial problems.…”
Section: Insights From Applying the Toolmentioning
confidence: 68%
“…This represents an advantage over other tools, validated in systems that are often benefiting from government programs, and therefore ignore some key attributes (e.g., policies, rules, and norms [16] and post-construction support [17]). In contrast, many systems in Colombia are managed by community organizations that mobilize themselves [61]. Thus, these key aspects cannot be ignored when assessing the sustainability of these systems.…”
Section: Insights From Applying the Toolmentioning
confidence: 99%
“…As policy attention and monetary budgets were directed to the most competitive cities, the reverse occurred in many rural areas which produced a continuous marginalisation. Rural residents suffer from a lack of access to services, whether this be health-care [36], infrastructure such as roads or water irrigation [37], broadband [38], public transport [39],…”
Section: Regional Development and The Geography Of Innovationmentioning
confidence: 99%